2007
DOI: 10.1016/j.neubiorev.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Activity- and use-dependent plasticity of the developing corticospinal system☆

Abstract: The corticospinal system (CS), critical for controlling skilled movements, develops during the late prenatal and early postnatal periods in all species examined. In the cat, there is a sequence of development of the mature pattern of terminations of corticospinal tract axons in the spinal gray matter, followed by motor map development of the primary motor cortex. Skilled limb movements begin to be expressed as the map develops. Development of the proper connections between CS axons and spinal neurons in cats d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 61 publications
(88 reference statements)
5
83
0
2
Order By: Relevance
“…Our finding of continuous development into adolescence also suggests that the window of opportunity for rehabilitation in children with neurodevelopmental disabilities is longer, assuming that the plasticity, i.e., "critical period," of the involved sensorimotor system remains high during this period (Armand et al 1997;Martin et al 2007). This interpretation is supported by findings in these children showing improvements in hand function with intense practice even in their adolescent years (Bonnier et al 2006;Eliasson et al 2006;Gordon et al 2007;Kuhtz-Buschbeck et al 2000).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our finding of continuous development into adolescence also suggests that the window of opportunity for rehabilitation in children with neurodevelopmental disabilities is longer, assuming that the plasticity, i.e., "critical period," of the involved sensorimotor system remains high during this period (Armand et al 1997;Martin et al 2007). This interpretation is supported by findings in these children showing improvements in hand function with intense practice even in their adolescent years (Bonnier et al 2006;Eliasson et al 2006;Gordon et al 2007;Kuhtz-Buschbeck et al 2000).…”
Section: Discussionmentioning
confidence: 64%
“…In parallel with the development of the ascending and descending pathways between brain and hand, there are striking developmental processes taking place in the brain gray and white matter during childhood up to adolescence, e.g., expansion of the white matter and pruning of the cortical gray matter (Asato et al 2010;Giedd et al 1999;Lebel and Beaulieu 2011;Lebel et al 2008;Martin et al 2007;Paus et al 1999). We (Ehrsson et al 2001) demonstrated earlier that there is a greater activity in the fronto-parietal sensorimotor areas during the control of smaller forces than larger forces, with control of larger forces associated with increased activity in the M1 region.…”
Section: Discussionmentioning
confidence: 99%
“…The active side maintains bilateral terminations at the expense of the silenced side. These experiments found that immobilization of an extremity also reduced innervation of the spinal cord by contralateral corticospinal tracts, suggesting that sensory activity from the limb also was important for plasticity of the developing corticospinal tracts [Martin et al, 2007].…”
Section: Plasticity In Children With Cerebral Palsymentioning
confidence: 92%
“…La evidencia apunta a una representación reducida en el área M1 del hemisferio derecho en comparación con el izquierdo en las personas diestras, relacionado con una disminución de la destreza de la mano no dominante. 54 En las áreas de asociación, las funciones especializadas relacionadas con la planificación no están muy desarrolladas, 55 probablemente debido a la fuerte demanda de "pistas" para seleccionar una determinada representación externa que involucra el procesamiento motor de la nueva exploración de situaciones. 56 El tema del procesamiento de la exploración de nuevas situaciones es consistente con la teoría de que el hemisferio izquierdo actúa en aspectos del movimiento en circuito abierto (en base a programas motores bien establecidos), mientras que el hemisferio derecho es crucial para todos los aspectos del movimiento en circuito cerrado (dependiendo de la retroalimentación sensorial).…”
Section: Contribuciones De Los Hemisferios Izquierdo Y Derecho En La unclassified